Stressed out? An investigation of whether allostatic load mediates associations between neighbourhood deprivation and health. (July 2018) - Prior, Lucy; Manley, David; Jones, Kelvyn
Abstract: Deprived neighbourhoods have long been associated with poorer health outcomes. However, many quantitative studies have not evidenced the mechanisms through which place 'gets under the skin' to influence health. The increasing prevalence of biosocial data provides new opportunities to explore these mechanisms and incorporate them into models of contextual effects. The stress pathway is a key biosocial mechanism; however, few studies have explicitly tested it in neighbourhood associations. This paper addresses this gap by investigating whether allostatic load, a biological response to chronic stress, mediates relationships of neighbourhood deprivation to physical and mental health. Data from UK Understanding Society is used to undertaken a multilevel mediation analysis. Allostatic load is found to mediate the association between neighbourhood deprivation and health, substantiating the biological mechanism of the stress pathway. More deprived areas are associated with higher allostatic load, and in turn worse allostatic load relates to poorer physical and mental health. Allostatic load is a stronger mediator of physical health than mental health, suggesting the stress pathway is more pertinent to explaining physical health gradients. Heterogeneity in the results between physical and mental health suggests more research is needed to disentangle the biosocial processes that could be important to health and place relationships. Highlights: Demonstration of the stress pathway in a multilevel, neighbourhood framework. Mediation methodology explicitly tests the link between neighbourhoods and health. Allostatic load mediated the neighbourhood deprivation-health relationship. Stronger support for the stress pathway for physical health than mental health.